2019
DOI: 10.3233/jpd-191721
|View full text |Cite
|
Sign up to set email alerts
|

Brain-First versus Gut-First Parkinson’s Disease: A Hypothesis

Abstract: Parkinson's disease (PD) is a highly heterogeneous disorder, which probably consists of multiple subtypes. Aggregation of misfolded alpha-synuclein and propagation of these proteinacious aggregates through interconnected neural networks is believed to be a crucial pathogenetic factor. It has been hypothesized that the initial pathological alpha-synuclein aggregates originate in the enteric or peripheral nervous system (PNS) and invade the central nervous system (CNS) via retrograde vagal transport. However, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
250
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(263 citation statements)
references
References 117 publications
(150 reference statements)
9
250
2
2
Order By: Relevance
“…Neuronal and systemic alterations of mtDNA have also been documented in AD [29,30], suggesting a possible common pathogenic mechanism. This aspect is supported by a recent study on neuromolecular imaging that brings the etiology of Parkinson's to the gastrointestinal tract via beta amyloid [31]. It has been previously reported that peripheral blood samples from AD patients exhibited an increased presence of variants in 89.7% of nucleotide positions (np) along the whole mtDNA sequence when compared to control subjects [30].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Neuronal and systemic alterations of mtDNA have also been documented in AD [29,30], suggesting a possible common pathogenic mechanism. This aspect is supported by a recent study on neuromolecular imaging that brings the etiology of Parkinson's to the gastrointestinal tract via beta amyloid [31]. It has been previously reported that peripheral blood samples from AD patients exhibited an increased presence of variants in 89.7% of nucleotide positions (np) along the whole mtDNA sequence when compared to control subjects [30].…”
Section: Introductionmentioning
confidence: 78%
“…Diagnostic accuracy varies considerably depending on disease duration (lower on first visit), age, clinician expertise, and increasing understanding of this pathology. In this context, advances in live imaging, such as neuromolecular imaging, could improve the understanding as well as diagnosis of PD [31,86]. Often, failure in recognizing other pathologies causing neurodegenerative disorder or secondary parkinsonism as well as the absence of a true progressive parkinsonian disorder are common causes of diagnostic error [85].…”
Section: Discussionmentioning
confidence: 99%
“…Here we adopt an idea of paper that patients with PD contain highly heterogeneous symptoms and display capricious involvement of different neuro-regions during the early phases of disease and this heterogeneity can be partly explained by de ning PD into a PNS-rst and a CNS-rst subtype [27]. According to this review, PD patients with olfactory function early impaired onset may possible belong to the PNS-rst subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus was decreased in individuals with possible RBD, whereas an increase in PD patients has previously been shown repeatedly. It is possible that subtypes of prodromal PD exist with varying involvement of the gut (e.g., RBD representing a subtype with early autonomic denervation) 47 . Also, the microbiome may (differentially) change over time, i.e.…”
Section: Discussionmentioning
confidence: 99%